2004
DOI: 10.1021/ol036341+
|View full text |Cite
|
Sign up to set email alerts
|

Biocidal Activity of Polystyrenes That Are Cationic by Virtue of Protonation

Abstract: [structure: see text] Poly(1) kills bacteria (Gram-positive and -negative) and lyses human erythrocytes; this biocidal profile is similar to that of the peptide toxin mellitin. Poly(1) has antibacterial activity comparable to that of a potent derivative of the host defense peptide magainin II, but lacks magainin's selectivity for bacteria over erythrocytes. An analogous N-quaternized polymer, poly(3), is less biocidal than poly(1), suggesting that reversible N-protonation leads to greater biocidal activity tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(129 citation statements)
references
References 27 publications
4
122
0
3
Order By: Relevance
“…In addition to the homopolymers, the random, alternating and block copolymers can be prepared in a designed manner. 42,43 Thus, the spatial distributions of cationic centers and hydrophobic groups are able to be rationally adjusted. Yoon and co-workers prepared block copolymers of polystyrene-bpoly(4-vinyl pyridine) and random copolymers of poly(styrene-r-4-vinyl pyridine), both bearing 4-vinyl pyridinium units as the cationic groups.…”
Section: Topological Designsmentioning
confidence: 99%
“…In addition to the homopolymers, the random, alternating and block copolymers can be prepared in a designed manner. 42,43 Thus, the spatial distributions of cationic centers and hydrophobic groups are able to be rationally adjusted. Yoon and co-workers prepared block copolymers of polystyrene-bpoly(4-vinyl pyridine) and random copolymers of poly(styrene-r-4-vinyl pyridine), both bearing 4-vinyl pyridinium units as the cationic groups.…”
Section: Topological Designsmentioning
confidence: 99%
“…To address these issues, a newer approach has been to design synthetic polymers mimicking the functions and structural features of the less toxic host defense peptides. This approach was successfully applied to the development of new types of polymer antimicrobials over the last decade, including copolymers of β-lactams [27], polynorbornenes [28], polymethacrylates [29,30], and polystyrenes [31]. Further fine-tuning of the polymers' physiochemical properties by modifying the cationic functionality, amphiphilic balance, and polymer sizes has yielded favorable improvements in antimicrobial activity and selective toxicity to bacteria relative to human red blood cells [30,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies reported antibiotics designed to follow the mechanism of natural AMPs, for example, peptides composed of ␣-amino acids (15)(16)(17), ␤-amino acids (18,19), peptoids (20), aromatic oligomers (21)(22)(23)(24), and synthetic polymers (25)(26)(27). Previously, we designed a series of arylamide foldamers that showed potential for both activity and selectivity (21).…”
mentioning
confidence: 99%